(untitled) (Jurnal Penelitian, 2024)
This article focuses on al-‘Aql al-Siyasi al-‘Arabi’s work and its relevance. It also touches the political phenomenon in Indonesia during 2016-2019 concerning ““NKRI Bersyariah (Sharia Republic of Indonesia Unitary State)” discourse supported by FPI and “khilafah” discourse supported by HTI. The research method employed was qualitative one involving library research viewed from Pierre Bourdieau’s perspective on habitus, field and distinction, and helped with interactive model of data analysis encompassing data reduction, data display, and conclusion drawing/verifying. The result shows that al-Jabiri views qabilah, ghanimah and aqidah as the habituated keywords since pre-Islam times. The temperament was manifested into the fighting for realizing the ideologies (aqidah) of “NKRI bersyariah” initiated by FPI qabilah, and “khilafah” (transnational) initiated by HTI qabilah. These ideologies basically are the capitalism movement trading Islam (ghanimah) to interest group. The incarnation of al-Jabiri’s terminology can be relevant to Indonesian political phenomenon.